Barriers to Understanding Posed by Biology School Textbooks and How to Lower Them Using Easy Language (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2023)
As texts in biology classes can contain many barriers to understanding, the concept of Easy Language (‘Leichte Sprache’) is currently discussed for use in schools. This article analyses comprehensibility barriers in standard school textbooks and highlights how translations into Easy Language can be realized and how they correspond to the educational standards. Overall, such translations seem to be promising, although some aspects still need further research and discussion.Da Texte im Biologieunterricht viele Verständlichkeitsbarrieren enthalten können, wird derzeit das Konzept der Leichten Sprache für den Einsatz in Schulen diskutiert. Der Artikel stellt exemplarisch Ergebnisse einer Analyse von Verständlichkeitsbarrieren in Schulbuchtexten vor. Er geht auch der Frage nach, inwiefern Übersetzungen in Leichte Sprache realisierbar sind und ob dieseden Kerncurricula entsprechen. Die Übersetzungen scheinen vielversprechend zu sein, auch wenn einige Aspekte diskussionswürdig sind.
Keywords: Easy Language; barriers to understanding; biological education; Leichte Sprache; Verständlichkeitsbarrieren; Biologieunterricht